Influence of nano powder mixed dielectric fluid on surface finish in micro electro discharge machining of zirconia - Ali, Mohammad Yeakub; Sabur, Abdus; Maleque, Md. Abdul (Bentham Science Publishers, 2017)
Background: Powder mixed dielectric fluid is being used recently to cut difficult to cut ceramic materials such as aluminium oxide (Al2O3) and zirconium oxide (ZrO2) where process development and optimization are found to be critical issues. Object: This paper investigates and compares the average surface roughness (Ra) in micro electrical discharge machining (EDM) of electrically nonconductive zirconium oxide (ZrO2) ceramic using clean and tantalum carbide (TaC) nano powder mixed kerosene dielectric fluid. Method: The design of experiment was applied by response surface methodology with face centred composite design. The gap voltage, capacitance and concentration of TaC powder are considered as the variable parameters for the investigation while other conditions are kept constant. Results: The study shows that the powder concentration has a significant negative effect on the average surface roughness of ZrO2. Conclusion: The optimized values of gap voltage and powder concentration are found to be 100 pF, 94.4 V and 6.3 g/l, respectively for a minimum surface roughness in micro-EDM of ZrO2. Without powder introduction, a minimum Ra surface roughness of 170 nm achieves 100 pF and 81 V.